Exploring Teachers’ Experience in the Implementation of Giving Merit Points to Students Participating in Extracurricular Activities - Agnes Pacas; Mario F. Alayon; Wilson Al D. Ramin; Krizzia Lou C. Alviso; Julie Kaye B. Bercaiso (Global READ Center, 2026)
This qualitative case study examined how senior high school teachers implement merit-point systems for students’ participation in extracurricular activities, focusing on the bases for awarding points, students’ observed responses, and strategies for ensuring consistency, fairness, and transparency. Although extracurricular participation is widely recognized as part of holistic student development, limited research has examined how merit-point systems are actually implemented at the senior high school level, particularly in terms of standardization, fairness, and evidence-based awarding practices. Seven (7) senior high school teachers whose students participated in extracurricular activities served as participants. Data were gathered through open-ended interviews that explored teachers’ experiences, perspectives, and practices in awarding merit points. Findings revealed that students commonly participated in sports and athletics, performing arts, student government, and school clubs or organizations. Teachers awarded merit points based on active participation, competition level, demonstrated achievement, and sustained commitment. To ensure fairness, they relied on clear criteria, verified participation, and equitable treatment. Teachers also observed enhanced motivation, perceived recognition, and strengthened academic confidence among students after receiving merit points. Based on these findings, the study proposes a standard operating procedure to promote consistent, transparent, and effective merit-point implementation.